Między galerią handlową, ratuszem i bazyliką. Miejsca charakterystyczne centrów śląskich miast w percepcji społecznej - Bierwiaczonek, Krzysztof (Studia Etnologiczne i Antropologiczne, 2010)
The centre can be considered one of the most universal categories in human thought. In the context of the city one can say that the centre is one of the spacious archetypes. In European cities of a long duration, centres have been determined by market squares, being economically and symbolically significant, as well as connected with power. Among those who paid attention to it were Aleksander Wallis, Bohdan Jałowiecki, Charles Landry, Leon Dyczewski, whose conceptions constitute a theoretical basis of this article. The empirical part of the text presents selected findings of sociological studies conducted in five Silesian cities, both those having a traditional central space with the market square (Rybnik, Bytom) and the ones which do not have such a centre (Tychy, Ruda Śląska). The attention was focused on those elements of the centre which in a social perception are regarded to be important. The studies show that the repertoire of places important in the centre of various cities is very similar. What dominates are places connected with the sacred, power and new spaces of the sacred and entertainment. What differs, however, is the quality of these places. Market squares still play an important part in the social perception. The market square and its closest surroundings in Rybnik are an example of a cultural area in the sense given to it by Aleksander Wallis. The cities which do not have market squares, on the other hand, are clearly deprived of attractive public spaces.